2013
DOI: 10.9775/kvfd.2012.7691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Holes of Various Sizes on Fracture Rates in Sheep Femurs

Abstract: SummaryDefects in long bones are known to lead to increased risk of pathologic fracture. Holes weaken bones and increase the risk of fracture during bending, especially on exposure to torsional forces. Here, we investigated the effect of holes of varying numbers and sizes drilled into sheep femur bones on the resistance of the bone to torsional forces. Ninety-six fresh sheep femur bones were allocated to 8 groups, which were further subdivided into 4 groups of 3 bones each. In each group, 1 to 4 holes ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…They found that the torsional strength and bending strength decreased to 60 % in bones with one screw hole as compared with intact bones. Olcay et al [19] also reported that the bone strength decreased in relation to the diameter of the screw hole. These results support our findings, as only 2 of 58 bones had bone defects and both were refractured after implant removal.…”
Section: Refracture Ratementioning
confidence: 94%
“…They found that the torsional strength and bending strength decreased to 60 % in bones with one screw hole as compared with intact bones. Olcay et al [19] also reported that the bone strength decreased in relation to the diameter of the screw hole. These results support our findings, as only 2 of 58 bones had bone defects and both were refractured after implant removal.…”
Section: Refracture Ratementioning
confidence: 94%
“…This effect is highlighted in mechanical work involving ovine femora with varying numbers and sizes of drill-holes. 18 Torsional resistance significantly decreased with increasing number of defects, albeit defect size was still noted to be the most important factor influencing failure strength. 18 Flexural properties of intact feline femora measured in this study are consistent with previously reported values.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to our screw-hole model, previous studies used bicortical drill-holes for the experimental defect. 5,6,8,[16][17][18] Area and polar moment of inertia are geometric functions of stiffness based on the object's cross-sectional profile to resist bending and torsional deformation respectively. Histomorphometry of 4 mm screw-holes in ovine pedicles showed between 14.2 and 37.4 µm 2 of bone were left within the screw-thread interface, depending on pilot hole diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During orthopaedic operations, drilling is the common process and heat generated in bone is inevitable 1 . The heat is a serious clinical concern because of its potential to cause bone damage and bad osseointegration in the implantation processes.…”
mentioning
confidence: 99%